Reduktion des Frakturrisikos unter Denosumab bei postmenopausalen Frauen in Abhängigkeit der Behandlungsbedürftigkeit nach DVO-Leitlinie 2009 - Hadji, P.; Bock, O.; Resch, H.; Kraenzlin, M.; Wang, A; Steinle, T.; Eisen, C (Osteologie, 2013)
In der FREEDOM-Studie konnte gezeigt werden, dass Denosumab 60 mg s. c. alle sechs Monate vs. Placebo bei postmenopausalen Frauen mit Osteoporose nach 36 Monaten das relative Risiko für vertebrale und nonvertebrale Frakturen sowie proximale Femurfrakturen um 68 %, 20 % und 40 % senkt (1). In einer Post-hoc-Analyse wurden nun die Teilnehmerinnen der FREEDOM-Studie entsprechend DVO-Leitlinie als behandlungsbedürftig (81 %) bzw. nicht behandlungs-bedürftig (19 %) eingestuft. Für die behandlungsbedürftige Subgruppe ergaben sich hierbei mit 67 %, 23 % und 41 % vergleichbare relative Risikoreduktionen. Auch in der nicht behandlungsbedürftigen Subgruppe reduzierte Denosumab das relative Risiko für neue vertebrale Frakturen um 75 % vs. Placebo (p = 0,0004); die Zahl der nonvertebralen Frakturen und proximalen Femurfrakturen unterschied sich hier zwischen den Behandlungsarmen nicht signifikant. Diese Auswertung zeigt, dass mehr als 80 % der FREEDOM-Population auch nach DVO-Leitlinie behandlungsbedürftig war und die für Denosumab gezeigten Frakturreduktionen auch unter Anwendung der DVO-Leitlinie in der täglichen Praxis erwartet werden können. Die deutliche Reduktion des Risikos für neue vertebrale Frakturen unter Denosumab auch in der Gruppe der nicht behandlungsbedürftigen Patienten ist ein bemerkenswerter Befund, der im Hinblick auf mögliche Konsequenzen für den Schwellenwert der DVO-Leitlinie bzw. für einen frühzeitigen effektiven Einsatz von Denosumab näher analysiert werden sollte.Data from the FREEDOM trial showed that denosumab 60 mg given subcutaneously every six months to postmenopausal women with osteoporosis reduces the relative risk for new vertebral fractures by 68 %, for nonvertebral fractures by 20 % and for hip fractures by 40 % at 36 months compared with placebo (1). Here we present results of a post hoc analysis to assess the proportion of the FREEDOM population at need for a specific osteoporosis treatment in accordance to DVO guideline (10-year risk for vertebral and hip fractures > 30 %), and the effect of denosumab on fracture risk in patients above or below this threshold for a specific osteoporosis treatment as defined by DVO. Participants of the FREEDOM trial were classified as “recommended for treatment” and “no need for treatment” based on the captured risk factors defined by the DVO guideline. Accordingly, 81 % or 6,323 out of 7,808 patients were classified as “recommended for treatment” according to DVO guideline (denosumab: 80.5 %; placebo: 81.4 %). Relative risk reductions for new vertebral (67 %, p < 0.0001), non-vertebral (23%, p = 0.0051), and hip fractures (41 %, p = 0.0353) in the subgroup of patients “recommended for treatment” were similar to the above-mentioned risk reductions in the entire FREEDOM population. In the subgroup of patients classified as “no need for treatment' ” according to DVO guideline, denosumab reduced the relative risk for new vertebral fractures by 75 % vs. placebo (p = 0.0004). The respective number of non-vertebral and hip fractures showed no significant differences between treatment groups. The relative risk for the combined endpoint of new vertebral and/or hip fractures after 36 months was reduced by 64 % (p < 0.0001) in the entire population, by 62 % (p < 0.0001) in the “recommended for treatment” group, and by 73 % (p = 0.0005) in the “no need for treatment” group, respectively. A sensitivity analysis (adjusting for an additional risk factor which might not have been captured, equivalent to a T-score shift by + 0.5) did not significantly change the results. This analysis comprised that the majority of the FREEDOM patients fulfilled the DVO criterion for a specific osteoporosis treatment and that the fracture risk reductions shown with denosumab could be expected in daily practice when applying the DVO guideline. The marked risk reduction for new vertebral fractures and for the combined endpoint of new vertebral and/or hip fractures with denosumab in the “no need for treatment” group according to DVO guideline is a striking result that should be further analyzed.
Keywords: Osteoporose; Frakturrisiko; DVO-Leitlinie; Denosumab